Effects of coenzyme Q10 encapsulated in nanoliposomes on wound healing processes after tooth extraction - Kosta Todorovic; Goran Jovanovic; Ana Todorovic; Aleksandar Mitic; Nenad Stojiljkovic; Sonja Ilic; Nikola Stojanovic; Slavica Stojnev (Elsevier, 2018)
Background/purpose: Tooth extraction is often followed by a number of different complications that demand additional treatment. In order to accelerate healing processes and decrease the complication occurrence various agents, growth factors, natural and synthetic antioxidants (e.g coenzyme Q10-CoQ10), are applied. Due to the partially known health-promoting effects of CoQ10 we decided to assess potential of it's encapsulated in nanoliposomes form on wound healing process following tooth extraction. Materials and methods: Effects of free and encapsulated form of CoQ10 on wound healing processes after tooth extraction in rats, 3 and 7 days following surgical procedure, was studied by means of tissue biochemical (myeloperoxidase activity and nitric oxide (NO) concentrations) and pathohistological analysis. Results: The obtained results indicate that the encapsulated form of CoQ10 compared to control and CoQ10 treated animals statistically significantly decreases inflammatory process estimated through myeloperoxidase activity and NO concentrations, as well as based on histopathological analysis 3 and 7 days following surgery. Conclusion: The results of this study unequivocally prove that the encapsulation of CoQ10 in nanoliposomes enhances CoQ10 activity by accelerating wound healing process after tooth extraction.